2021
DOI: 10.1098/rstb.2020.0337
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm in dyadic interactions

Abstract: This review paper discusses rhythmic interactions and distinguishes them from non-rhythmic interactions. We report on communicative behaviours in social and sexual contexts, as found in dyads of humans, non-human primates, non-primate mammals, birds, anurans and insects. We discuss observed instances of rhythm in dyadic interactions, identify knowledge gaps and propose suggestions for future research. We find that most studies on rhythmicity in interactive signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 153 publications
(231 reference statements)
1
21
0
Order By: Relevance
“…The SMS-like behaviour observed in insects and frogs is reminiscent of SMS in humans, primates and birds, with the calls of other individuals serving as the pacing signal for the synchronizing animal. However, it must be noted that this behaviour typically occurs within the context of natural or simulated signal exchanges, and may, therefore, be more comparable with studies of interpersonal synchronization in humans, as discussed elsewhere (see [131], this volume).…”
Section: Rhythm Productionmentioning
confidence: 57%
“…The SMS-like behaviour observed in insects and frogs is reminiscent of SMS in humans, primates and birds, with the calls of other individuals serving as the pacing signal for the synchronizing animal. However, it must be noted that this behaviour typically occurs within the context of natural or simulated signal exchanges, and may, therefore, be more comparable with studies of interpersonal synchronization in humans, as discussed elsewhere (see [131], this volume).…”
Section: Rhythm Productionmentioning
confidence: 57%
“…For instance, one paper in this special issue develops newly detailed frequency-specific descriptions of a kind of synchrony, and then uses them to make new inferences about musical and rhythmic behaviour in humans [37]. The examples of [38] on the interactive vocalizations of primates are also enhanced by a frequency-specific perspective: fig. 1C of [38] shows coordination of not only the timings but also the pitches of the calls of a pair of indris, a feature which would not be revealed without the additional statistical detail provided by the frequency-specific techniques of that paper (spectrograms).…”
Section: Resultsmentioning
confidence: 99%
“…The examples of [38] on the interactive vocalizations of primates are also enhanced by a frequency-specific perspective: fig. 1C of [38] shows coordination of not only the timings but also the pitches of the calls of a pair of indris, a feature which would not be revealed without the additional statistical detail provided by the frequency-specific techniques of that paper (spectrograms). Sheppard, Zhao and colleagues [26,39,40] developed detailed frequency-specific measures of synchrony in population ecology which provided major inferential benefits.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have identified vocal turn‐taking in meerkats (Demartsev et al, 2018) and some primate species (e.g., Lepilemur edwardsi , Méndez‐Cárdenas & Zimmermann, 2009). These findings have been used to suggest that turn‐taking is one of the basic foundations of social communication across a variety of different species (de Reus et al, 2021).…”
Section: Introductionmentioning
confidence: 99%